Continuous time controller design - Balasubramanian, R. (Ramachandran) 1942-1985 (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1989)
This book covers theoretical methods for the design of continuous time controllers for linear multivariate systems. It is intended for use by those wishing to build on a first course in control systems, either to expand their knowledge as practicing engineers or as post graduate students doing higher degrees in control engineering. Based on the material used in graduate courses taught by professor Balasubramanian at the University of New Brunswick, this book brings together state space and frequency domain design methods for linear multivariable systems. It compares Their similarities and highlights the advantages or disadvantages of the various approaches for particular applications. Divided into eleven chapters, this book covers in some depth: state space design methods, frequency domain methods for multivariable systems, characteristic locus design and stochastic control problems.